201k views
1 vote
If A =
\left[\begin{array}{ccc}cosx&-sinx\\sinx&cosx\end{array}\right], then show that
(A^(-1) )^(-1)

1 Answer

3 votes

Given:

The matrix is:


A=\begin{bmatrix}\cos x&-\sin x\\\sin x&\cos x\end{bmatrix}

To show:


(A^(-1))^(-1)=A

Solution:

If a matrix is:


M=\begin{bmatrix}a&b\\c&d\end{bmatrix}

Then,


M^(-1)=(1)/(ad-bc)\begin{bmatrix}d&-b\\-c&a\end{bmatrix}

We have,


A=\begin{bmatrix}\cos x&-\sin x\\\sin x&\cos x\end{bmatrix}

Using the above formula, we get


A^(-1)=(1)/((\cos x)(\cos x)-(-\sin x)(\sin x))\begin{bmatrix}\cos x&\sin x\\-\sin x&\cos x\end{bmatrix}


A^(-1)=(1)/(\cos^2x+\sin^2x)\begin{bmatrix}\cos x&\sin x\\-\sin x&\cos x\end{bmatrix}


A^(-1)=(1)/(1)\begin{bmatrix}\cos x&\sin x\\-\sin x&\cos x\end{bmatrix}


A^(-1)=\begin{bmatrix}\cos x&\sin x\\-\sin x&\cos x\end{bmatrix}

Now, the inverse of
A^(-1) is:


(A^(-1))^(-1)=(1)/((\cos x)(\cos x)-(\sin x)(-\sin x))\begin{bmatrix}\cos x&-\sin x\\\sin x&\cos x\end{bmatrix}


(A^(-1))^(-1)=(1)/(\cos^2x+\sin^2x)\begin{bmatrix}\cos x&-\sin x\\\sin x&\cos x\end{bmatrix}


(A^(-1))^(-1)=(1)/(1)A


(A^(-1))^(-1)=A

Hence proved.

User Adithya Shetty
by
5.7k points